PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN INFRASTRUKTUR, UTILITAS DAN TRANSPORTASI - Ramadhan, Rhonal; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to evaluate the influence of intellectual capital to the financial performance which is proxy by earning per share and return on equity in the annual financial performance which has been prepared by the infrastructure, utility, and transportation companies which are listed in Indonesia Stock Exchange. The data collection technique has been done by performing documentation in the form of annual financial statement which has been obtained from the official website of Indonesian Stock Exchange. The population is infrastructure, utility and transportation companies which are listed in Indonesia Stock Exchange (IDX) in 2012-2015 periods. The sample selection technique has been done by using purposive sampling based on specific criteria so that 14 infrastructure, utilities, and transportation companies have been selected as samples so that 56 observations have been obtained. The analysis method has been carried out by using simple linear regressions with the SPSS application (Statistical Product and Service Solutions). The result of this research shows that intellectual capital gives positive influence to the earning per share and intellectual capital give positive influence to the return on equity.Keywords: Intellectual capital, Financial performance, Earning Per Share, Return On Equity